Antagonists of growth hormone-releasing hormone inhibit growth of androgen-independent prostate cancer through inactivation of ERK and Akt kinases - Rick, Ferenc G. (National Academy of Sciences, 2012)
The management of castration-resistant prostate cancer (CRPC) presents a clinical challenge because of limitations in efficacy of current therapies. Novel therapeutic strategies for the treatment of CRPC are needed. Antagonists of hypothalamic growth hormone-releasing hormone (GHRH) inhibit growth of various malignancies, including androgen-dependent and independent prostate cancer, by suppressing diverse tumoral growth factors, especially GHRH itself, which acts as a potent autocrine/paracrine growth factor in many tumors. We evaluated the effects of the GHRH antagonist, JMR-132, on PC-3 human androgen-independent prostate cancer cells in vitro and in vivo. JMR-132 suppressed the proliferation of PC-3 cells in vitro in a dose-dependent manner and significantly inhibited growth of PC-3 tumors by 61% (P < 0.05). The expression of GHRH, GHRH receptors, and their main splice variant, SV1, in PC-3 cells and tumor xenografts was demonstrated by RT-PCR and Western blot. The content of GHRH protein in PC-3 xenografts was lowered markedly, by 66.3% (P < 0.01), after treatment with JMR-132. GHRH induced a significant increase in levels of ERK, but JMR-132 abolished this outcome. Our findings indicate that inhibition of PC-3 prostate cancer by JMR-132 involves inactivation of Akt and ERK. The inhibitory effect produced by GHRH antagonist can result in part from inactivation of the PI3K/Akt/mammalian target of rapamycin and Raf/MEK/ERK pathways and from the reduction in GHRH produced by cancer cells. Our findings support the role of GHRH as an autocrine growth factor in prostate cancer and suggest that antagonists of GHRH should be considered for further development as therapy for CRPC.